2022
DOI: 10.26434/chemrxiv-2022-5x360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-separation propensity of non-ionic amino acids in peptide-based complex coacervation systems

Abstract: Uncovering the sequence-encoded molecular grammar that governs the liquid–liquid phase separation (LLPS) of proteins is a crucial issue to understand dynamic compartmentalization in living cells and the emergence of protocells. Here, we present a model LLPS system that is induced by electrostatic interactions between anionic nucleic acids and cationic oligolysine peptides modified with 12 different non-ionic amino acids, with the aim of creating an index of ‘phase-separation propensity’ that represents the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The aromaphilicity index is expected to be useful for understanding various phenomena occurring in proteins, peptides, and amino acids. Aromaphilicity was recently suggested to be related to the mechanism of liquid-liquid phase separation of proteins and peptides [19][20][21], which suggests the potential application of the index for describing and understanding residue-residue interactions in proteins and peptides. A for future directions includes the design of amino acid sequences in proteins and peptides as biopharmaceuticals on the basis of the aromaphilicity index.…”
Section: Perspective: the Practical Use Of The Aromaphilicity Indexmentioning
confidence: 99%
“…The aromaphilicity index is expected to be useful for understanding various phenomena occurring in proteins, peptides, and amino acids. Aromaphilicity was recently suggested to be related to the mechanism of liquid-liquid phase separation of proteins and peptides [19][20][21], which suggests the potential application of the index for describing and understanding residue-residue interactions in proteins and peptides. A for future directions includes the design of amino acid sequences in proteins and peptides as biopharmaceuticals on the basis of the aromaphilicity index.…”
Section: Perspective: the Practical Use Of The Aromaphilicity Indexmentioning
confidence: 99%
“…Lim et al 15 observed condensates in 23-residue peptides rich in histidine and tyrosine. Akahoshi et al 16 observed condensation with polyA 15 ssDNA and K 7 X 3 peptides, where X represents several different residues. Tang et al 17 conducted an exhaustive computational survey of all dipeptide sequences and experimentally demonstrated liquid droplets of QW.…”
Section: Introductionmentioning
confidence: 99%